"On the Streets, We Don't Have Time to Get Treated as We are Trying to Survive": The Stories of Mentally Ill Homeless Persons Residing in a Community-based Health Centre in the City of Tshwane. Issue 3 (1st October 2020) - Mooa, Ramadimetja S.; Moagi, Miriam M.; Hugo, Jannie
ABSTRACT: Globally, one of the main causes of street homelessness is the reality of chronic mental illness. In societies where mental illness is misunderstood, stigmatized, or sparsely treated, or where treatment is inaccessible for the poor, the link between street homelessness and chronic mental illness becomes even greater. This article considers the stories of specific individuals living with chronic mental illness in the City of Tshwane, South Africa, which caused them to be homeless. It also reflects on the infrastructure available to persons with chronic mental illness who are homeless, and recommends ways to scale up and replicate good practices, while transforming unutilized or ineffective infrastructure. Data were collected through drawings and naïve sketches from participants housed at a community-based health centre in Tshwane which acts as a "bridge" between mental health institutions, home and/or even the street. Ten participants voluntarily participated in the study and five in-depth interviews were held with the staff members at the centre. The insights indicated that the ripple effects of a deinstitutionalization plan for a sustainable policy package, could improve the quality of life for mentally ill homeless persons while housed in such community-based centres.